2020
DOI: 10.15406/jpcpy.2020.11.00662
|View full text |Cite
|
Sign up to set email alerts
|

Mental health issues of fire personnel: an exploratory study

Abstract: The primary goal of the current study was to add to the literature regarding mental health implications of fire service membership. In the present study, 100 fire personnel were selected working in Haryana state of India. The DSM V cross cutting Questionnaire was used to assess mental health issues of the fire personnel and the results suggested that firefighters self-reported greater posttraumatic symptomatology on anger and substance issue domain of the test. In addition, the firefighters reported more distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…More particularly, in our study, the 12 firefighters with probable PTSD seem to have more pronounced mean levels of depression and hostility in contrast to participants without probable PTSD (still, paranoid ideation was the dimension with a higher score for both groups). These results are not surprising since Sindhu et al (2020) postulated that rates of PTSD and depression in firefighters and other rescue workforces are higher than in the general population, and their study with 100 Indian firefighters found higher levels of substance issues, anger, and sleep problems, followed immediately by depression. Similar results evidencing depressive symptoms among firefighters were found across studies, for example, in Australian (e.g., Harvey et al, 2016), Chinese (Sun et al, 2020), Greek (Psarros et al, 2018), and U.S. samples (Stanley et al, 2017).…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…More particularly, in our study, the 12 firefighters with probable PTSD seem to have more pronounced mean levels of depression and hostility in contrast to participants without probable PTSD (still, paranoid ideation was the dimension with a higher score for both groups). These results are not surprising since Sindhu et al (2020) postulated that rates of PTSD and depression in firefighters and other rescue workforces are higher than in the general population, and their study with 100 Indian firefighters found higher levels of substance issues, anger, and sleep problems, followed immediately by depression. Similar results evidencing depressive symptoms among firefighters were found across studies, for example, in Australian (e.g., Harvey et al, 2016), Chinese (Sun et al, 2020), Greek (Psarros et al, 2018), and U.S. samples (Stanley et al, 2017).…”
Section: Discussionmentioning
confidence: 88%
“…Interestingly, these results are in line with the case study analyzed in Becker et al's (2022) study as the two Portuguese firefighters studied (male and female, volunteer and career firefighters, respectively) scored higher in those two dimensions of the BSI at baseline. Furthermore, as cited by Sindhu et al (2020), in 1990, Mitchell evidenced 12 characteristics of personality among emergency service workers (including firefighters) that can contribute to cumulative stress, for example, a need to be in control, obsessive perfectionism, and other compulsive behaviors. Psarros et al (2018) found that the perception of fear of imminent death during critical firefighting operations and neuroticism may precipitate the development of PTSD in these workers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations